Kajian Pragmatik terhadap Kesantunan Berbahasa Siswa Sekolah Dasar - Gita Pratiwi; Silvina Noviyanti; Nazurty; Nuratikah Najua Pauzi; Nanda Gusfira; Nadia Oktaviani Asmi; Ulfa Fitri Fazhira (STKIP Subang, 2026)
his study aims to examine the politeness of language used by elementary school students from a pragmatic perspective. The focus of the study includes forms of language politeness, types of politeness violations, and factors influencing students’ language use in communication within the school environment. The research employs a literature study method with a descriptive qualitative approach. Data were obtained from various secondary sources such as books, academic journals, and previous research relevant to pragmatics and language politeness. Data analysis was conducted using content analysis by identifying, classifying, and synthesizing research findings. The results indicate that elementary school students have a basic understanding of language politeness, such as the use of polite expressions and the ability to adjust language based on the interlocutor. However, violations of politeness are still frequently found, particularly in the use of overly direct language and the lack of respectful expressions. Family, school, and digital media environments play significant roles in shaping students’ language behavior. Therefore, contextual learning and continuous habituation of polite language use are necessary. This study contributes to the development of pragmatic studies and serves as a foundation for improving language learning quality in elementary schools. Keywords: pragmatics, language politeness, elementary school students, literature study